2019
DOI: 10.1038/s41598-019-52016-9
|View full text |Cite
|
Sign up to set email alerts
|

Declining abundance of coral reef fish in a World-Heritage-listed marine park

Abstract: One of the most robust metrics for assessing the effectiveness of protected areas is the temporal trend in the abundance of the species they are designed to protect. We surveyed coral-reef fish and living hard coral in and adjacent to a sanctuary zone (SZ: where all forms of fishing are prohibited) in the World Heritage-listed Ningaloo Marine Park during a 10-year period. There were generally more individuals and greater biomass of many fish taxa (especially emperors and parrotfish) in the SZ than the adjacent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Babcock et al (2008) compared results from surveys in 2006-07 with those of previous surveys (Ayling & Ayling 1987, Westera et al 2003 and found lower abundance of lethrinids, suggesting that their abundance has declined over time. Ten years of surveys by Vanderklift et al (2019) support this, finding parallel declines inside and outside the Mandu Sanctuary Zone. The abundance of Labridae (wrasses) and Chaetodontidae (butterflyfish) have also declined, while other families, including parrotfish and surgeonfish, do not appear to have changed.…”
Section: Mobile Inhabitants Of the Reef: Fish And Invertebratesmentioning
confidence: 70%
See 2 more Smart Citations
“…Babcock et al (2008) compared results from surveys in 2006-07 with those of previous surveys (Ayling & Ayling 1987, Westera et al 2003 and found lower abundance of lethrinids, suggesting that their abundance has declined over time. Ten years of surveys by Vanderklift et al (2019) support this, finding parallel declines inside and outside the Mandu Sanctuary Zone. The abundance of Labridae (wrasses) and Chaetodontidae (butterflyfish) have also declined, while other families, including parrotfish and surgeonfish, do not appear to have changed.…”
Section: Mobile Inhabitants Of the Reef: Fish And Invertebratesmentioning
confidence: 70%
“…However, the abundance of corals in some sheltered locations south of Point Cloates has declined steadily since 2011 (Holmes et al 2017), and localised decreases in coral cover have also occurred north of Point Cloates (e.g. Vanderklift et al 2019). Cyclones might have caused some mortality, but the declines are coincident with major warming events and seem most likely to be caused by water temperatures exceeding thermal thresholds.…”
Section: Corals: the Foundation Of The Reefmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research uncovered potential shortfalls in the terrestrial natural WHA estate, documenting an average 63% increase in human pressures (Allan et al 2017), potentially compromising the outstanding universal value of several sites. Increasing human pressures have also been documented within marine natural WHAs (mnWHA), including a 22% decline in coral reef fish abundance per year in the Ningaloo Marine Park WHA (Vanderklift et al 2019) and a loss of around 50% of coral within the Great Barrier Reef WHA (De’ath et al 2012). The human impacts driving these declines, however, have yet to be quantified across the global mnWHA estate.…”
Section: Introductionmentioning
confidence: 99%